Serpiginous Granuloma Annulare: A Case Report - Sharma, Rajni; Manvi, Sujaya (International Journal of Innovative Research in Medical Science, 2018)
Granuloma annulare (GA) is a benign inflammatory skin condition of unknown etiology. Various clinical forms of GA including localized, generalized, subcutaneous, patch and perforating types, have been described. Although the etiology and pathogenesis of granuloma annulare are obscure, there is much evidence for an immunological mechanism. Precipitating factors are insect bites, sunburn, photochemotherapy, drugs, physical trauma, acute phlebitis and sepsis after surgery.[1] Some authors have proposed that it might be associated with a variety of underlying conditions such as thyroid disorders, diabetes mellitus and positive tuberculin skin test.[2] For definitive diagnosis, a biopsy should be performed. We report a case of generalized GA with serpiginous borders on the dorsal aspects of the hands and arms along with an association with diabetes.